Archives 101 - Hamill, Lois, 1957- (American Association for State and Local History book series., 2021)
"Archives 101 is a guidebook for people who care for historical records, photographs, and collections but do not have the appropriate professional training. Lois Hamill provides practical, step-by-step guidance for managing all facets of archival collections, from acquisition, arrangement, and description to storage and security"--